THE LATEST ASPECTS OF PIG MINERAL NUTRITION - Usenko, S. O.; Siabro, A. S.; Bereznytskyi, V.I.; Chukhlib, Ye. V.; Slynko, V.G.; Myronenko, O.I. (Scientific Progress & Innovations, 2019)
The paper deals with modern ideas concerning pig mineral nutrition. The latest data on the influence of micro-elements on physiological processes in the body, through the activity of enzymes, hormones and vita-mins are presented. It has been stated that micro-elements are involved in the biosynthesis of proteins, nucle-ic acids, ensure lipid metabolism and synthesis of separate hormones of the thyroid gland, pancreas and pi-tuitary gland. Iron, zinc, copper, selenium and magnesium have been found to have a significant effect on the productivity of animals and play a special role in the reproductive capacity of sows. With insufficient or ex-cessive content of minerals in the diet, there is a decrease in the vital and reproductive functions of the ani-mal organism. The new directions of pig mineral nutrition have been considered and it has been found out that, unlike salts of metals, the chelate compounds of micro-elements in the digestive tract interact better with feed biologically active substances, have lower toxicity and are almost completely absorbed in the intes-tine, retaining their properties. Various sizes and shapes of nanoparticles enhance their ability to bind pro-teins, nucleic acids, penetrate cellular organelles, integrate into membranes, and thus affect the functions of bio-structures more effectively. This enables to reduce the doses of introducing the salts of micro-elements into the organism, which prevents the environmental pollution with metals. It has been determined that due to a wide spectrum of microelements’ chelate compounds action reproductive function indices are signifi-cantly improved: sows prolificacy, heavy farrowing, litter weight and milk productivity increase, the preser-vation of piglets before and after weaning improves; sperm motility, survival and heat resistance of breeding boars, improving sperm fitness for long-term storage are increased. Including chelate micro-elements in the diet contributes to the increase in pig live weight, slaughter output, and improvement of meat physical-chemical properties.